Galvanic ternary Fe-Co-W coatings: structure, composition and magnetic properties - Yermolenko, I.Yu.; Ved', M.V.; Sakhnenko, N.D.; Fomina, L.P.; Shipkova, I.G. (Functional Materials, 2018)
Principles of Fe-Co-W alloys electrodeposition from complex Fe (III) based citrate electrolytes are discussed. The effect of both current density and pulse on/off time on the quality, composition and surface morphology of the electrolytic alloys were determined. The application of pulsed electrolysis provides increasing ungsten content up to 13 at.%, at current efficiency of 70-75 %. Globular surface of Fe-Co-W coatings is caused by refractory metals incorporation, and crystalline and amorphous parts of structure are visualized by X-ray spectroscopy, including inter-metallic phases Co₇W₆, Fe₇W₆ along with α-Fe and Fe₃C. The coherent-scattering region size of the amorphous part is 2-8 nm. Magnetic characteristics of amorphous Fe-Co-W coatings were measured in dependence of deposition ime. The conclusion was made that the content of magnetic phase in upper layers of coating is greater than in the bottom ones due to decreasing W atom concentration.